The role of Nagorno-Karabakh in the shaping of Armenian and Azeri identity | El rol de Nagorno-Karabagh en la formación de la identidad armenia y azerí - Torres, Ricardo Juan (Mural Internacional, 2021)
The paper discusses the effect of the 19th century rebirth of Armenian nationalism in the Ottoman or Western Armenia and Russian or Eastern Armenia and of Azeri nationalism in Russian Azerbaijan with its ramifications in Iran and Ottoman Turkey on the formation of Armenian and Azeri identity from the late 1800s to the present and the key role of Nagorno-Karabakh - called Artsakh by the Armenians- from the beginning of the 20th century, using the theories of Anthony D. Smith. At the time of the disintegration of the USSR, the reinforcement of Armenian and Azeri identity over Nagorno-Karabakh and the Armenian victory in the first war and the armed peace generated by the 1994 ceasefire made it inevitable that a second war would take place unless a political compromise – that never happened – was reached. Keywords: nationalism, identity, Nagorno-Karabakh. RESUMEN El trabajo analiza el efecto del renacimiento del nacionalismo armenio en el siglo XIX en la Armenia otomana u occidental y la Armenia rusa u oriental y del nacionalismo azerí en el Azerbaiyán ruso con sus ramificaciones en Irán y la Turquía otomana en la formación de la identidad armenia y azerí desde finales del 1800 hasta el presente y el papel clave de Nagorno-Karabagh - llamado Artsaj por los armenios - desde principios del siglo XX, usando las teorías de Anthony D. Smith. En el momento de la desintegración de la URSS, el refuerzo de la identidad armenia y azerí sobre Nagorno-Karabagh y la victoria armenia en la primera guerra y la paz armada generada por el alto el fuego de 1994 hicieron inevitable que ocurriera una segunda guerra a menos que se llegara a un compromiso político, lo que no sucedió. Palabras-clave: nacionalismo, identidad, Nagorno-Karabagh. Recebido em: 15 jun. 2021 | Aceito em: 18 out. 2021.